A Magnetically Recoverable Fe3O4–NH2–Pd Sorbent for Capture of Mercury from Coal Derived Fuel Gas - Lina Han (Nature Portfolio, 2017)
Abstract A sort of magnetical material named Fe3O4–NH2–Pd was prepared by loading varying amounts of immobilizing Pd on the surface of the magnetic Fe3O4–NH2 microspheres. This magnetical material was used firstly for capturing Hg° from coal derived fuel gas based on its recoverability. The experimental results showed that the loading Pd on the amine-functionalized magnetite nanoparticles can greatly improve the efficiency of removing Hg° at a high temperature range between 200 and 300 °C. The magnetic Fe3O4–NH2–Pd sorbent with 5% Pd loaded exhibited significantly high activity and stability in capturing Hg°, affording over 93% capture efficiency at 200 °C for more than 8 hrs. Compared to the Fe3O4–NH2 sorbent that converted the Hg° as HgS, this Fe3O4–NH2–Pd sorbent can remove the Hg° by forming Pd-Hg amalgam and HgS. In addition, the experimental tests indicated that the as-synthesized Fe3O4–NH2–Pd sorbent still showed stable magnetic properties after two regeneration cycles in removing Hg°, which provided the opportunity for preparing a recyclable sorbent which can be easily separated and recovered for Hg° removal.